Case report: Novel use of the conventional method- chemical nail avulsion may be effective for treatment of green nail syndrome - Yu, Qian; Wang, Yuanyuan; Yang, Hong; Li, Wei; Yang, Lianjuan (Frontiers in Medicine, 2022)
Green nail syndrome (GNS) is a triad of green discoloration of the nail plate, proximal paronychia, and distal onycholysis. Pseudomonas aeruginosa is known to be the most common causative agent; however, there is no unified standard for the diagnosis and treatment of GNS. Thus, treatment is challenging and often refractory. Here, we report three representative cases with different predisposing factors, including trauma-related, occupation-related, and onychosis-related GNS. Patients with GNS accompanied by onycholysis were instructed to undergo chemical nail avulsion combined with topical antibiotics, and favorable curative effects were observed in all cases. Chemical nail avulsion with urea powder as a conventional method may be an effective treatment for GNS and warrants clinical generalization.